The two sides of temporal orienting: facilitating perceptual selection, disrupting response selection. - Correa, A; Cappucci, P; Nobre, A; Lupiáñez, J (2010)
Would it be helpful to inform a driver about when a conflicting traffic situation is going to occur? We tested whether temporal orienting of attention could enhance executive control to select among conflicting stimuli and responses. Temporal orienting was induced by presenting explicit cues predicting the most probable interval for target onset, which could be short (400 ms) or long (1,300 ms). Executive control was measured both by flanker and Simon tasks involving conflict between incompatible responses and by the spatial Stroop task involving conflict between perceptual stimulus features. The results showed that temporal orienting facilitated the resolution of perceptual conflict by reducing the spatial Stroop effect, whereas it interfered with the resolution of response conflict by increasing flanker and Simon effects. Such opposite effects suggest that temporal orienting of attention modulates executive control through dissociable mechanisms, depending on whether the competition between conflicting representations is located at perceptual or response levels.